Application of Saptopakram in Vranashopha Management- A Review - Ujjawal Shivhare,; Mrigank Shekhar,; Shailendra,; Tina Singhal, (International Journal of Ayurveda and Pharma Research, 2022)
Vrana i.e., wound and its management has prime importance in surgical practice. Vranashopha has peculiar clinical features and is rapidly spreading pathological condition. The disease isn’t easy to treat even if a doctor knows its stages very well. So the deep and exact knowledge about the Vranashopha and its stages is must for a good doctor. Acharya Sushruta has mention and explained 7 major procedures (Saptopakram) for Vranashopha management which includes the management at its initial stage (Amavastha) through the wound stage (Vranavastha) till the management of the complications of the healed wound (Vaikritapaham). We can categorized these procedures as the first 3 procedure can be used for Amavastha and Pachyamanavastha both, the 4th for Pakwavastha alone, 5th & 6th for the stage of wound and the 7th for the management of complications of healed wound. The description of Saptopakrama is described for both Aam and Pakvasopha means it included Nija and Agantuja both type of Vrana.In this review article, we have tried to describe different types of Shopha, their Lakshanas (signs & symptoms), and their management according to Susruta Samhita in Ayurveda. There are some efforts have also been carried out to collect, discuss and describe the Ayurvedic concept of Saptopakram.